2016
DOI: 10.1016/j.topol.2016.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Topological properties of the group of the null sequences valued in an Abelian topological group

Abstract: Following [23], denote by F0 the functor on the category TAG of all Hausdorff Abelian topological groups and continuous homomorphisms which passes each X ∈ TAG to the group of all X-valued null sequences endowed with the uniform topology. We prove that if X ∈ TAG is an (E)-space (respectively, a strictly angelic space or aŠ-space), then F0(X) is an (E)-space (respectively, a strictly angelic space or aŠspace). We study respected properties for topological groups in particular from categorical point of view. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Proof. (i) If A is not precompact, Theorem 5 of [3] implies that A has an infinite uniformly discrete subset C, i.e., there is a neighborhood U of zero in E such that c−c ′ ∈ U for every distinct c, c ′ ∈ C. Thus, by Lemma 2.1 of [19], C and hence also A are not functionally bounded, a contradiction.…”
Section: Proof Of Theorem 12mentioning
confidence: 98%
“…Proof. (i) If A is not precompact, Theorem 5 of [3] implies that A has an infinite uniformly discrete subset C, i.e., there is a neighborhood U of zero in E such that c−c ′ ∈ U for every distinct c, c ′ ∈ C. Thus, by Lemma 2.1 of [19], C and hence also A are not functionally bounded, a contradiction.…”
Section: Proof Of Theorem 12mentioning
confidence: 98%
“…Außenhofer [2] proved that every locally quasi-convex Schwartz group respects compactness. For a general and simple approach to the theory of properties respected by M AP topological groups see [24].Let (E, τ ) be a locally convex space (lcs for short), E ′ the dual space of E and let τ w = σ(E, E ′ ) be the weak topology on E. Set E w := (E, τ w ). An lcs E is said to have the Schur property if E and E w have the same convergent sequences, i.e., S(E) = S(E w ).…”
mentioning
confidence: 99%
“…Thirdly, Rolewicz [26] observed that the complete metrizable group F 0 (T) is monothetic (see a proof of this fact in [11, pp. 20-21] or in [18]). So monothetic Polish groups need not be compact nor discrete.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the last two arguments show that the groups of the form F 0 (X) represent a nice source of (counter)examples in different areas of topological algebra. For other important properties of the functor F 0 see [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation